Predictors of chest drainage complications in trauma patients - MENDES,CECÍLIA ARAÚJO (2018)
ABSTRACT Objective: to identify predictors of chest drainage complications in trauma patients attended at a University Hospital. Methods: we conducted a retrospective study of 68 patients submitted to thoracic drainage after trauma, in a one-year period. We analyzed gender, age, trauma mechanism, trauma indices, thoracic and associated lesions, environment in which the procedure was performed, drainage time, experience of the performer, complications and evolution. Results: the mean age of the patients was 35 years and the male gender was the most prevalent (89%). Blunt trauma was the most frequent, with 67% of cases, and of these, 50% were due to traffic accidents. The mean TRISS (Trauma and Injury Severity Score) was 98, with a mortality rate of 1.4%. The most frequent thoracic and associated lesions were, respectively, rib fractures (51%) and abdominal trauma (32%). The mean drainage time was 6.93 days, being higher in patients under mechanical ventilation (p=0.0163). The complication rate was 26.5%, mainly poor drain positioning (11.77%). Hospital drainage was performed in 89% of cases by doctors in the first year of specialization. Thoracic drainage performed in prehospital care presented nine times more chances of complications (p=0.0015). Conclusion: the predictors of post-trauma complications for chest drainage were a procedure performed in an adverse site and mechanical ventilation. The high rate of complications demonstrates the importance of protocols of care with the thoracic drainage.